Adaptive FCM Clustering Routing Algorithm Based on PSO Optimization - Liu, Yue; Liang, Ying (2024 2nd International Conference on Signal Processing and Intelligent Computing (SPIC), 2024)
To solve the problems of large node energy consumption and missing data transmission path in Marine sensor networks, a clustering routing algorithm utilizing particle swarm optimization (PSO-DAFCA) was introduced. The algorithm uses fuzzy C-means method of particle swarm optimization to optimize cluster head selection and cluster member configuration, and selects the best cluster head by dynamically updating cluster center. During the data transmission phase, combined with the global search ability of cat swarm optimization algorithm, the path evaluation function based on energy and distance parameters is introduced to determine the optimal transmission route. Simulation results indicate that the PSO-DAFCA algorithm can enhance network energy efficiency, prolong network lifespan, and improve the real-time accuracy of marine environmental monitoring.